Development of postural balance in Brazilian children aged 4-10 years compared to young adults - Luiz Fernando Cuozzo Lemos; Ana Cristina de David; Carlos Bolli Mota (Revista Brasileira de Cineantropometria e Desempenho Humano, 2016)
The aim of the present study was to analyze the development of postural balance in 4- to 10-year-old Brazilian children, compared to a group of young adults under normal and deprived visual conditions. Body sway was assessed through average velocity and sway range at the center of pressure (CoP) in the anteroposterior and medio-lateral directions, obtained on a force platform (AMTI, Inc.). Sample was composed of 153 children (of seven different age groups) and 47 adults. Inter-group comparisons were performed using one-way ANOVA and Tukey’s post-hoc test at 5% significance level. The results showed that starting at 9 and 10 years of age, CoP velocity and displacement values for children were similar to values for adults under restricted visual conditions; however, there were differences between children and adults. The findings suggest that visual stimulation plays a prominent role in the balance of individuals up to 10 years of age, with significant evidence that postural balance is not fully developed up to that age.